A Photoetching‐After‐Growth Approach for the Synthesis of Nanocrystal Heterostructures Exhibiting Tunable Dual‐Band Emission. Issue 1 (3rd December 2019) - Lim, Sung Jun; Kim, Wonjung; Shin, Seung Koo
Abstract: Introduced herein is a new strategy for synthesizing sophisticated colloidal semiconductor nanostructures with targeted optical properties by combining a conventional colloidal growth (bottom‐up) process and a postgrowth photoetching (top‐down) process. To demonstrate the utility of such photoetching‐after‐growth approach, a complex quantum dot (QD)–quantum rod (QR) dual quantum‐confined domain nanocrystal heterostructure (NCH) is engineered which exhibits bright dual‐band emission precisely tunable in a broad visible region. (CdSe/CdS)/ZnS/CdSe QD/barrier/multi‐QR NCHs consisting of a single CdSe/CdS QD core and multiple CdSe QR branches with a wide‐bandgap ZnS barrier between them are prepared through a multistep colloidal growth. The as‐synthesized NCHs show a single emission band from QR; however, after photoetching, NCHs begin to display bright dual emission bands, a high‐energy emission band from QR in addition to the low‐energy emission band from QD. While the QD emission at 586 nm is determined by colloidal growth conditions, that of QR emission is precisely tunable in the 500–585 nm range by quantum‐size‐selective photoetching using a wavelength‐tunable laser. Notably, the QR emission bandwidth decreases to ≈20 nm, which is close to that of a single CdSe nanorod, emphasizing a significant quantum‐size‐focusing effect of the photoetching process. Abstract : A photoetching‐after‐growth approach for engineering sophisticated nanocrystal heterostructures with targeted optical properties combining both a conventional colloidal growth process and a controllable photoetching process is explained. The dual‐band emission spectrum of a quantum dot/barrier/multiquantum rod heterostructure can be precisely controlled in a broad visible window by using the quantum‐size‐selective photoetching.